Implementation of a Quality Management System in E-Learning Services: A Case Study of Google Classroom - Tjerie Pangemanan; Joshua Ebenazher Hutabarat; Nazril Alhafid Damopolii; Syeriel Vioneta Lompoliu; Chessy C. Kapahang (Publikasi Indonesia, 2026)
The digital transformation of education has led to the widespread adoption of e-learning platforms, with Google Classroom becoming one of the most widely used tools globally. However, high adoption rates do not automatically guarantee service quality, necessitating a systematic quality management approach. This study analyzes the application of Quality Management System (QMS) principles to the Google Classroom e-learning service based on ISO 9001:2015. The research employs a literature review method, mapping Google Classroom features to the seven QMS principles: customer focus, leadership, engagement of people, process approach, continual improvement, evidence-based decision-making, and relationship management. The findings indicate strong support for user-centered design, structured instructional workflows, and continual improvement. However, gaps remain in formal quality documentation, internal audit mechanisms, and structured management review processes. Full ISO 9001:2015 compliance requires educational institutions to complement Google Classroom’s operational capabilities with formal quality documentation, audit mechanisms, and structured vendor relationship management.